PENGARUH PENGURANGAN KARYAWAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PT. TELKOM (PERSERO) WITEL ACEH - Hasyim Hasbi; Syarifah Akmal; Yohana Dian Putri (Universitas Dirgantara Marsekal Suryadarma, 2026)
PT Telkom Indonesia (Persero) Tbk Witel Aceh experienced a reduction in the number of employees due to organizational transformation and human resource restructuring. The number of permanent employees decreased from 51 in 2022 to 22 in 2025, representing a decline of 59%. This condition potentially increases workload and may affect employee performance. This study aims to analyze the effect of employee reduction and work motivation on employee performance at PT Telkom Indonesia (Persero) Tbk Witel Aceh. A quantitative approach was employed using a survey method with a census technique involving all 22 permanent employees. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that all measurement indicators meet validity and reliability criteria. The structural model shows an R-square value of 0.63, indicating that employee reduction and work motivation explain 63% of the variance in employee performance. Hypothesis testing reveals that both variables have a positive and significant effect on employee performance. This study concludes that effective management of employee reduction and enhancement of work motivation are important to maintain employee performance during organizational transformation